Fire Safety Management in a Typical Higher Institution in Nigeria - Anyanwu, Brilliance O.; Akaranta, Onyewuchi; Nwaogazie, Ify L. (New Ideas Concerning Science and Technology Vol. 6, 2021)
The scarcity of literature on fire safety awareness and practice and the lack of consideration of human decisions and organizational failures that contribute to fire disasters in schools formed the thrust for this study. The study was carried out to determine the level of fire safety awareness and the level of fire safety implementation in the University of Port Harcourt. Secondary data were collected from the fire service unit of the University to show the number of fire occurrences and major causes of fire incidents in the University. The primary data were collected by means of questionnaires administered to 250 persons out of which 220 were retrieved representing a response rate of 88%. Twenty questions were designed as questionnaire parameters; the first ten are to assess the level of fire safety awareness amongst respondents in University of Port Harcourt while the second ten are to evaluate the fire safety implementation /practice in the University. The responses are rated as strongly agree (4), agree (3), disagree (2) and strongly disagree (1). Data analyses were facilitated via the evaluation of Kendall’s coefficient of concordance (w), that is, the degree of agreement amongst the respondents. The results revealed an average level of awareness and a low implementation /practice level amongst the respondents. Lack of awareness on the emergency number to call in the event of fire, lack of fire safety policy, lack of knowledge on the different types of portable fire extinguishers, inadequate provision and inspection of firefighting equipment, lack of inspection and review of past fire incidents, nonchalant attitude of turning off electrical appliances after use, electrical installations/repair not being handled by competent persons and the staff and students not having adequate information, instruction and training on fire safety are the gaps identified. Kendall’s analysis revealed a high degree of agreement amongst the respondents on both fire safety awareness (0.78) and fire safety implementation /practice (0.90), respectively. Thus, the study recommends a fire safety organogram for delegation of duties, training of staff and students on basic fire safety, provision and inspection of fire preventive and protective methods, employment of competent personnel to handle electrical works to ensure the protection of lives, assets, environment and reputation of the institution.